Character Moderasi Beragama pada Siswa Sekolah Menengah Keatas Melalui Pembelajaran Pendidikan Agama Islam di MA Darut Taqwa - Akhmad Fadilah; Muhammad Saifulah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Through education, students' personalities will be formed into culturally qualified and responsible individuals. The role of religion in Islamic education in school institutions is a form of manifestation to preserve Islamic religious values for the next generation, so that they can continue to function along with developments over time. PAI is an instructive interaction by a teacher to equip students with learning, information and motivation in carrying out Islamic education. The success of religious and character education for students can occur because of cooperation between teachers, parents and the school. The method in this research is descriptive qualitative research. This type of research was chosen to understand in depth how the process of developing religious moderation character education is carried out through Islamic Religious Education (PAI) learning. In an effort to realize character education, MA Darut Taqwa has a program containing character values to build students' character for the better. The mandatory programs implemented at MA Darut Taqwa to shape student character are flag ceremonies, praying, saying greetings, greeting each other among school members, in order to form friendship and community service activities. Teachers play a role as maintainers, implementers and administrators of education. Within the family sphere, parents are the main role models for children in showing the values of religious moderation.